1989
DOI: 10.1093/sleep/12.5.413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Positive Airway Pressure on Phasic Events of REM Sleep in Patients with Obstructive Sleep Apnea

Abstract: In patients with obstructive sleep apnea and associated rapid-eye-movement (REM) sleep deprivation and disruption, the first night of nasal continuous positive airway pressure (CPAP) is often associated with increases in REM sleep time and REM density (REM rebound). The amount of REM rebound, however, varies considerably. We sought to characterize the magnitude of REM rebound and to determine what factors determine individual differences in REM rebound with initial CPAP treatment. Twenty-six patients with slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 0 publications
2
27
0
1
Order By: Relevance
“…Patients with OSAS have a typically disrupted sleep structure with an increased number of arousals and increased proportion of NREM sleep stages 1 and 2 and depressed slow wave sleep (SWS) as well as REM sleep. CPAP was shown to eliminate obstructive eventrelated arousals, to increase SWS and REM sleep and to decrease NREM sleep stages 1 and 2, even during the ®rst night [22,23]. The present results proved that the titration with PPAP affected the sleep structure in the same manner, as did CPAP.…”
Section: The Effectiveness Of Ppapsupporting
confidence: 72%
“…Patients with OSAS have a typically disrupted sleep structure with an increased number of arousals and increased proportion of NREM sleep stages 1 and 2 and depressed slow wave sleep (SWS) as well as REM sleep. CPAP was shown to eliminate obstructive eventrelated arousals, to increase SWS and REM sleep and to decrease NREM sleep stages 1 and 2, even during the ®rst night [22,23]. The present results proved that the titration with PPAP affected the sleep structure in the same manner, as did CPAP.…”
Section: The Effectiveness Of Ppapsupporting
confidence: 72%
“…Four hundred sixty-seven articles were screened, 58 were evaluated in full-text form, and 14 studies met the established criteria (Brillante et al 2012;Koo et al 2012;Kushida et al 2011;Yaegashi et al 2009;Osuna et al 2008;Drake et al 2003;Verma et al 2001;Randerath et al 2001;Parrino et al 2000;Yamashiro and Kryger 1995;Lamphere et al 1989;Aldrich et al 1989;Issa and Sullivan 1986;Collard et al 1996). Eleven of the 14 studies noted a statistically significant increase in amount of REM sleep during the titration night, compared to the baseline sleep study.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, sleep becomes more consolidated with an increase in the duration of REM sleep compared to the diagnostic study. REM rebound (Brillante et al 2012;Koo et al 2012;Kushida et al 2011;Yaegashi et al 2009;Osuna et al 2008;Drake et al 2003;Verma et al 2001;Randerath et al 2001;Parrino et al 2000;Yamashiro and Kryger 1995;Lamphere et al 1989;Aldrich et al 1989;Issa and Sullivan 1986;Collard et al 1996) is the polysomnographic phenomenon of substantial increase in duration of REM sleep in a patient with untreated OSA when first undergoing CPAP titration. Similarly, some patients may exhibit an increase in the duration of slow wave sleep called slow wave sleep rebound (Brillante et al 2012;Osuna et al 2008;Verma et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Wake time and N2 decreased with the improvement of REM duration and REM cycling. Earlier studies report decrement of N1/N2 stages with consequent rebound of N3 and REM sleep period during the first CPAP night [32,33]. Kondo et al [34] found that beneficial effects of CPAP treatment on sleep architecture lasts till the device is used for controlling apneas.…”
Section: Discussionmentioning
confidence: 99%